Temporary Taxes as Macro-Economic Stabilizers - Dolde, Walter (American Economic Review, 1979)
An analysis of the effectiveness of temporary tax changes requires both a theoretical framework and its careful empirical implementation. Reflex rejection of the usefulness of temporary taxes with a vague appeal to the permanent income hypothesis is as inappropriate as blind acceptance naively based on the high correlation between consumer expenditure and current disposable income. The remainder of this paper sketches a theoretical framework for analysis with an eye towards implementation, reviews the evidence for the United States, and provides a summary. The analysis concludes that temporary taxes are useful and effective stabilization instruments, though there is no reason to favor them over tax changes of an indefinite duration. Space limitations prevent discussion of taxes other than personal income taxes. Expenditure taxes, for which intertemporal substitution effects augment income effects on current expenditure, have a greater effect per dollar of deficit.